State of research data management in latin american universities 2022 - Amado Tineo, José Percy; Olivera Batista, Dianelis; Machado Rivero, Manuel Osvaldo; Vancauwenbergh, Sadia; Limaymanta Álvarez, César Halley; Gonzales Cam, Celso Morelan; Peralta González, María Josefa; García Cartaya, Arelexys Antonia; Ballivian Blanco, Andrea; Meneses Placeres, Grizly; Chávez, Georgina Aurelia; Salvatierra Melgar, Angel; et al. (euroCRIS, 2024)
Research Data Management is based on the so-called FAIR Principles of data, whose fundamental objective is to make data freely findable, accessible, interoperable and reusable, thus encouraging the adoption of these principles by institutions has become a standard of Best Practices. Universities, in their role as teaching and research centers, should embrace such principles in order to develop science of higher quality, accessibility, visibility and impact. RDMS-LatAm identifies the project entitled: "Development of a Strategy for Research Data Management in Higher Education and Scientific Institutions within the Latin American context". An initiative that has brought together the Universidad Central "Marta Abreu" de las Villas (CUBA) as coordinator, Universidad Nacional Mayor de San Marcos (Peru), Universidad Católica de Bolivia “San Pablo” and the University of Hasselt (Belgium), with the support of VLIR-UOS (Belgium). The objective of this project is: "To develop capacities to adopt good practices on Research Data Management in the Latin American context". So far, RDMS-LatAm's actions have allowed the development of diagnostics on data management in member universities, the elaboration of policy proposals, the training of teachers, researchers, librarians and undergraduate and graduate students, as well as the development of a new instrument to identify research data management practices in the institutions. In addition, collaborative relationships have been established with other centers that can benefit from the results achieved.
Keywords: Análisis de datos; Procesamiento de datos; Protección de datos; Cuba; Bolivia; Peru